Potensi Antihiperlipidemia Ekstrak Etanolik Daun Bayam Merah (Amaranthus tricolor L.) Terstandar secara in Vivo Berdasarkan Parameter LDL (Low Density Lipoprotein) - Dimas Adhi Pradana; Faras Sophia Rahmah; Tri Ratna Setyaningrum (Jurnal Sains Farmasi & Klinis, 2016)
This study aims to determine the potential for curative therapy ethanolic extract of red spinach leaves (Amaranthus tricolor L.) standardized to decrease LDL levels in vivo. Animal model used in this study were 30 male Wistar rats aged 2-3 months were randomly divided into 6 groups include normal control, negative control, positive control and three doses ratings eksktrak. Induction of hyperlipidemia using poloxamer on day 1st and propylthiouracil on day 5th to day 18th. The positive control groups were given by simvastatin and the treatment group were given three doses of the extract variations on each - each group ie 200 mg / kg, 400 mg / kg, and 800 mg / kg rat. Ethanolic extract of red spinach leaves that are used have been through a standardized test based on specific parameters and non-specific. Determination of plasma LDL levels was done 3 times, day 0 (baseline), day 4th (after induction process) and day 19th (after treatment). The results obtained show the ethanolic extract of red amaranth (Amaranthus tricolor L.) standardized at a dose of 800 mg / kg body weight can lower LDL levels statistically significant (p <0.05) compared with normal and negative group. It can be concluded that the ethanolic extract red spinach leaves standardized has activity as a curative therapy for hyperlipidemia.